Steroid–steroid interactions in biological membranes: Cholesterol and cortisone. (July 2019) - Khondker, Adree; Hub, Jochen S.; Rheinstädter, Maikel C.
Highlights: The lipid bilayer can promote crystallization of cortisone at high local concentrations associated with steroid flares, common side effects associated with corticosteroid treatment. The presence of cholesterol in the membranes was found to suppress cortisone-induced membrane thinning and cortisone transnucleation. Cortisone displaces cholesterol off its canonical position in lipid bilayers. Cholesterol plays an important role in the ability of lipid bilayers to catalyze the formation of corticosteroid crystallites and the occurrence of steroid flares. Abstract: Steroid flares are common side effects associated with corticosteroid treatment, and have been recently theorized to be a consequence of drug crystallization. It was previously reported that the lipid bilayer can promote crystallization of cortisone at high local concentrations. Here, we studied the effect of cholesterol on this membrane induced cortisone crystallization. By combining x-ray diffraction and Molecular Dynamics simulations we observe that that the presence of cholesterol suppresses cortisone-induced membrane thinning and cortisone transnucleation. Cortisone located in the head-tail interface of the membranes also in the presence of cholesterol. The cholesterol molecules were found to be tilted and displaced towards the bilayer center as function of cortisone concentration, away from their canonical position. Our results show that membrane cholesterol may play an important role in the ability of lipid bilayers to catalyze the formation of corticosteroid crystallites.